2004
DOI: 10.1023/b:brea.0000018406.03679.2e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of LOH and Mitochondrial DNA Alterations in Ductal Lavage and Nipple Aspirate Fluids from High-risk Patients

Abstract: We describe a method for the isolation of free DNA from ductal lavage (DL) and nipple aspirate fluid (NAF), and its evaluation for the presence of LOH at the BRCA1 and FHIT genes and for mitochondrial DNA (mtDNA) mutations at the D310 marker, to improve early detection of breast cancer. We evaluated 26 DL and six NAF samples from 14 women of known BRCA1 status, who have no clinical evidence of breast tumors: nine mutation carriers and five non-carriers. LOH studies at the BRCA1 locus were possible in 19/26 DL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…One previous study has reported a LOH rate of 58% at the BRCA1 locus using free DNA from the ductal lavage supernatant of known BRCA1 carriers (12). Although Isaacs et al reported that the LOH results were consistent using the same DNA preparations, reproducibility between different aliquots was not commented upon.…”
Section: Resultsmentioning
confidence: 99%
“…One previous study has reported a LOH rate of 58% at the BRCA1 locus using free DNA from the ductal lavage supernatant of known BRCA1 carriers (12). Although Isaacs et al reported that the LOH results were consistent using the same DNA preparations, reproducibility between different aliquots was not commented upon.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, identical changes were detected in four of four urine sediments from patients with bladder cancer and in three of three fine needle aspirates of patients with breast cancer (Parrella et al, 2003). Nipple aspirate fluid has also mtDNA mutations in human cancer A Chatterjee et al yielded mitochondrial C-tract alterations in breast cancer patients (Isaacs et al, 2004) In another study, urine from five patients with bladder cancer and duodenal aspirates from four patients with pancreatic cancer were tested using the Mitochip array (Maitra et al, 2004). At least one cancer associated mitochondrial mutation was found in six of the nine body fluid samples.…”
Section: Mitochondrial Diagnostics Of Tumorsmentioning
confidence: 96%
“…For these reasons, evaluation of breast duct cells is an emerging technique for breast cancer risk assessment, and for the discovery of potential biomarkers which may serve as intermediate end points in trials of cancer prevention agents (28)(29)(30)(31)(32)(33)(34). Various minimally invasive methods exist for collecting breast duct cells, including nipple suction aspiration and random periareolar fine-needle aspiration; the finding of atypia in cells collected by each of these techniques has been associated with increased subsequent breast cancer risk (35,36).…”
Section: Introductionmentioning
confidence: 99%